Lembaran pesanan warisan - Siti Maimon Kamso-Wanrafaei. (Kajang, Selangor : Mayfield Strategic Management Consultancy, 2010)
Essays on commerce, social conditions, and education in Malaysia.
Includes bibliographical references.
In Malay.
Keywords: Education -- Malaysia; Malaysia -- Commerce; Malaysia -- Social conditions